MERAWAT INGATAN: FILOSOFI MARANTAU DI DALAM PANTUN-PANTUN MINANGKABAU - Zulfikarni Zulfikarni; Siti Ainim Liusti (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2020)
Wandering for Minangkabaunese people is to go away from their hometown to gain experience. After having successful, they have to return to their hometown in order to develop it and lift the dignity of their family and people. However, due to the current development, the goals of wandering has changed. The goals are not to: 1) because of the matrilineal system where men do not get inheritance property rights, only the right of managing. 2) Continuing the success of previous nomads and natural conditions. 3) Adding Life Experience (educational factors) 4) Improving the economic and social status of families and people, 5) marantau cino. All of these forms and reasons for wandering, each of which has its own philosophy for the people of Minangkabau which is conveyed through poems.